PEMANFAATAN MEDIA PEMBELAJARAN KREATIF UNTUK MENINGKATKAN MINAT BELAJAR SISWA MI/SD - Khusnul Khovia; Iis Hariska (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This research looks at how using creative learning tools can help increase the interest of elementary school students in their studies at MI Nur Muhammad Klakah Lumajang. This study used a descriptive qualitative method and followed a case study structure. The people who took part in the research were chosen on purpose based on specific criteria. Data was gathered by observing, talking to people, keeping records, and using questionnaires, and then it was studied using the interactive model developed by Miles and Huberman. Data validity was checked by using different sources and methods. The study shows that using creative learning tools like pictures, videos, games, and flashcards makes learning more engaging, fun, and meaningful. Students started to be more involved, excited, attentive, sure of themselves, and ready to take part in class discussions and activities. Creative learning media made it easier for students to understand learning materials by offering clear and interesting ways to experience the content. Even though there were many challenges like not enough resources, not enough tech help, not enough time to prepare, and differences in students' backgrounds, teachers kept changing the media to fit what the classroom needed. Creative learning materials help make learning more interesting for students and improve how well they learn in elementary school.